Preparation of high-entropy perovskite oxygen carrier and application thereof in chemical looping conversion
Patent Information
- Application Number
- CN202610882836.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-18
- Publication Date
- 2026-10-09
AI Technical Summary
[0019]目前,已开发的这些基于钙钛矿类载氧体的化学链循环反应体系还存在着很多方面的问题,这些问题的解决需要更多系统性的研发工作
[0033]1. 本发明以高熵钙钛矿类载氧体La1-xAx{Coy(B1B2B3…BN)1-y}O3-δ作为氧化还原循环活性材料,进行两步法化学链CH4部分氧化与CO2和/或H2O分解制备合成气与CO和/或H2,该高熵钙钛矿类载氧体与其他类型的载氧体材料相比,可以在较低温度下制备出更高产量的合成气(≤ 800oC,10-200 mL/g),且CH4部分氧化反应无积碳生成,合成气中H2/CO摩尔比接近理论比值n(H2)/n(CO)=2:1,合成气选择性高达100%,尤其适用于费托合成反正制备甲醇。
Smart Images

Figure CN122877704A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to an application of a two-step chemical chain method for the partial oxidation of CH4 and the decomposition of CO2 and / or H2O to prepare syngas and CO and / or H2, respectively. Specifically, it relates to the use of high-entropy perovskite oxygen carriers (La... 1-x A x {Co y (B1B2B3…B N ) 1-y}O 3-δ As a redox cycle active material, it converts CH4 and CO2 and / or H2O into syngas and CO and / or H2 through a two-step chemical chain reaction. This chemical chain reaction system utilizes high-temperature heat energy generated by solar thermal concentrating or industrial waste heat recovery as an energy source to efficiently convert CH4 and CO2 and / or H2O into high-value-added chemicals and chemical fuels (such as CO / H2). This chemical chain conversion technology has very broad application prospects in energy conservation, emission reduction, and environmental protection. Background Technology
[0002] With the rapid development of global industry, the consumption of primary energy has shown a strong growth trend. At present, the global energy consumption structure is still dominated by fossil fuels, and the proportion of renewable energy is relatively low. In particular, the greenhouse effect caused by global carbon emissions is receiving more and more attention. (Journal of Economic Perspectives, 2018, 32(4):53-72.). The unsustainability of fossil energy is becoming more and more obvious. The greenhouse effect and environmental pollution caused by the overuse of fossil energy are becoming increasingly prominent, making the research and development of clean and environmentally friendly renewable energy systems urgent. CH4 and CO2 are the main greenhouse gases, and their large-scale emissions have led to a serious greenhouse effect. Solar energy has many advantages such as being clean and pollution-free, inexhaustible, and renewable. Using solar energy to convert carbon dioxide and / or water into carbon monoxide and / or hydrogen and oxygen can avoid pollution problems at the source. In addition, using the high-temperature heat energy generated by focusing solar energy and / or industrial waste heat recovery to convert greenhouse gases CH4 and CO2 into high-value-added chemicals and chemical fuels that are easy to store can also mitigate the greenhouse effect. In recent years, the development and application of such science and technology have received widespread attention from the scientific research community and industry.
[0003] The two-step chemical loop recycling technology for partial oxidation of CH4 and decomposition of CO2 and / or H2O is a key technology integrating solar energy conversion and chemical fuel production. The core of this technology is to develop oxygen carrier catalysts that can efficiently convert CH4 and CO2, and it is also one of the hot topics in the current field of new energy development and research. The main steps of this recycling reaction system are: (1) The oxidized perovskite oxygen carrier first reacts with CH4 at a certain temperature (400-1000℃), and CH4 is partially oxidized into syngas. At the same time, the oxidized oxygen carrier is reduced to a reduced oxygen carrier rich in oxygen vacancy defects; (2) The reduced oxygen carrier rich in oxygen vacancy defects then reacts with CO2 and / or H2O at a certain temperature (400-1000℃), releasing CO and / or H2. At the same time, the reduced oxygen carrier is re-oxidized to the initial state, completing the regeneration and restoration. The specific chemical reaction equations are as follows (eq. 1-2):
[0004] <![CDATA[CO2 + Me x O y-δ → CO + Me x O y ]]> (2)
[0005] To date, many metal oxides with redox properties have been developed for chemical looping reactions involving the partial oxidation and decomposition of CH4 and CO2 and / or H2O. Most of these are complex, multi-step looping systems, with only a few metal oxides capable of completing the CO2 and / or H2O decomposition cycle in a two-step manner. Currently, the most studied two-step chemical looping reactive oxygen carriers are fluorite-type oxygen carriers, spinel-type oxygen carriers, and perovskite-type (ABO) oxygen carriers. 3-δ Metal oxide systems such as oxygen carriers.
[0006] Tink et al. (Canadian Journal of Technology, 1951, 29: 243-249.) first proposed the concept of chemical chain reaction in the 1950s. In chemical chain reaction, the reaction and regeneration of chemical substances are carried out in a cycle to achieve the goal of production or separation (Engineering, 2021, 7(01): 178-199.).
[0007] Xia et al. (Chemical Engineering Journal, 2024, 489.) reported a layered crosslinked Ni / CeO2 catalyst that exhibited excellent stability after continuous operation at 700 °C for 50 hours, with a CH4 conversion of 60% and a CO2 conversion of 73%. The sintering of Ni particles was suppressed because the migration and aggregation of Ni nanoparticles provided by the layered CeO2 nanosheets were restricted.
[0008] Appiagyei et al. (Chemical Engineering Journal, 2025, 507: 160684.) developed a composite structure of distorted spinel ferrite (mainly MgFeAlO4 and Fe3O4) and discrete oxides (MgO and Fe2O3). In a CH4 / CO2 chemical looping test at 900 °C, this oxygen carrier exhibited excellent performance, with an oxygen transfer capacity as high as approximately 19.8 mmol / g.
[0009] In perovskite oxygen carriers, A-site modification mainly falls into two categories: A-site doping modification and A-site defect modification. A-site doping is an important strategy for controlling the performance of perovskite oxygen carriers in chemically chained dry methane reforming (CL-DRM) (Applied Catalysis B: Environmental, 2015, 164: 371-379). The principle is to introduce a host ion (such as Gd) that interacts with the A-site (e.g., Gd). 3+ La 3+ Foreign cations with different valence states or radii (such as alkaline earth metals Sr) 2+ Ca 2+ Ba 2+ While maintaining the stability of the main crystal lattice, it enables controllable changes in the electronic structure, defect concentration, and oxygen migration ability of the oxygen carrier.
[0010] A-site doping is an important method for customizing efficient and stable perovskite oxygen carriers through a process of "composition design-structural fine-tuning-performance optimization".
[0011] Zhang et al. (ACS Catalysis, 2020, 10, 9420-9430.) reported La 1-x Sr x Fe 0.8 Al 0.2 O3 oxides increased the oxygen capacity from 1.0 mmol / g (x=0.1) to 2.7 mmol / g (x=0.5) through A-site regulation, while maintaining CO selectivity above 94%. Introducing A-site defects into perovskite ABO3 can increase the oxygen vacancy concentration through charge compensation, thereby improving the bulk oxygen diffusion coefficient and enhancing resistance to coking. Furthermore, the lattice distortion induced by A-site vacancies can lower the oxygen migration energy barrier, optimizing oxygen transport and surface reaction kinetics.
[0012] Zhu et al. (Green Chemical Engineering, 2025, 6, 102-115.) investigated the effects of SrFeO on... 3-δ High-performance Sr was successfully prepared by exploiting A-site defects. 0.98 Fe 0.7Co 0.3 O 3-δ A perovskite-structured oxygen carrier. In isothermal CL-DRM testing at 850 °C, this material achieved 87% CH4 conversion and 94% CO selectivity in the partial oxidation of CH4, followed by a syngas yield of 8.5 mmol / g and a CO yield of 4.2 mmol / g in the CO2 decomposition reaction. This strategy provides a simple and efficient pathway for chemical chaining or other redox processes to modulate the oxygen storage capacity, oxygen mobility, and oxygen vacancy concentration of perovskite-structured materials.
[0013] In perovskite oxygen carriers, B-site modification is mainly achieved through B-site doping, which is a key strategy for optimizing the performance of perovskite oxygen carriers in chemically linked methane dry reforming. The core of this strategy lies in using heterovalent or equivalent metal cations with specific catalytic, electronic, or structural functions (such as Ni). 2+ Co 3+ Al 3+ Ga 3+ Transition metal ions that partially replace the B site (e.g., ions) directly regulate the intrinsic reactive sites of the material.
[0014] Yin et al. (Green Chemical Engineering 2025, 6, 102-115.) studied LaMn 1− x B x O 3-δ (B = Fe, Co, Ni, x = 0.1, 0.2, 0.3) Perovskite was used as the oxygen carrier in CL-SMR. The results showed that doping with active metal elements altered the perovskite structure, increased the number of surface active centers, and increased oxygen vacancies. The activation of methane molecules on the carrier surface and the transport of oxygen ions in the bulk phase accelerated the activation of methane molecules on the oxygen carrier particle surface and the transport of oxygen ions in the bulk phase. Therefore, the doping of Fe, Co, and Ni improved the performance of LaMnO₂. 3+δ The rate of oxygen release was improved, and the order of improvement was Ni > Co > Fe. Substitution with Fe, Co, and Ni also improved the oxygen release, CO selectivity, and hydrogen yield of the catalyst.
[0015] Zhao et al. (Journal of Materials Chemistry A, 2019, 7(11): 6099-6112.) studied the use of LaBO3 (B=Co,Fe,Cu,Al) perovskite catalysts for methanol steam reforming (MSR). The results showed that LaCoO3 exhibited 100% methanol conversion and a methanol yield of 7.86 mol / min. -1 g -1It exhibits a significant hydrogen production rate and maintains stability at 600°C for over 40 hours.
[0016] High-entropy perovskite oxygen carriers (typically of the formula ABO3, where the A / B sites are composed of five or more elements) have an entropy greater than 1.5R. They exhibit unique application potential in chemically chained dry methane reforming (CL-DRM), with their core advantage stemming from their unique "high-entropy effect." This effect, through the synergy of lattice distortion, slow diffusion, and cocktail effects, endows the oxygen carrier with comprehensive properties surpassing those of traditional single or binary perovskites. (Science China Materials 2022, 65(10): 2711-2720.)
[0017] Akbar et al. (ACS Applied Nano Materials, 2026, 9: 2060-2073.) reported LnMn 0.2 Fe 0.2 Co 0.2 Ni 0.2 Cu 0.2 O3 (Ln = La, Ce, Pr, Nd, Sm, Gd) high-entropy perovskite oxygen carriers were synthesized via a sol-gel method and used in methane dry reforming reactions. Among the six rare-earth high-entropy perovskite oxygen carriers, LnMn... 0.2 Fe 0.2 Co 0.2 Ni 0.2 Cu 0.2 O3 exhibits the highest catalytic activity, with an H2 / CO ratio of 1. After 100 h of reaction, the conversion rate of CH4 is 86% and the conversion rate of CO2 is 90%.
[0018] Zhu et al. (Sustainable Energy & Fuels, 2024, 8: 5524-5534.) proposed preparing highly active oxygen carriers through functionally designed multi-metal doped manganese-based perovskite oxides. In SrMnO 3−δ Cu doping at the B-site exhibits a significant anti-coking effect during the high-temperature continuous CH4 / CO2 redox process. Ni doping at the B-site enhances methane activation performance, thus achieving high methane conversion. Furthermore, Ce doping at the A-site improves oxygen migration and enhances the partial oxidation of methane to H2 and CO, as well as the re-oxidation process of reduced perovskite oxides. Considering the combined effects of Cu, Ni, and Ce in SrMnO... 3−δ Through the role of doping, a multi-metal-doped perovskite oxygen carrier Sr was synthesized. 0.8 Ce 0.2 Mn 0.7 Cu 0.1 Ni 0.2 O3−δ The optimized perovskite oxide exhibited excellent performance after 30 redox cycles at 850 °C, with a methane conversion of 85% and a CO selectivity of 93%. During the redox reaction, transition metals such as Mn, Cu, and Ni agglomerated during reduction, but were restored to a well-dispersed state after re-oxidation with CO2.
[0019] Currently, the developed chemical chaining reaction systems based on perovskite oxygen carriers still face many challenges, requiring further systematic research and development to resolve. Furthermore, the A- and B-sites of perovskite oxygen carriers can be extensively doped, providing ample room for the creation and modification of novel perovskite oxygen carrier materials. These chemical chaining reaction systems based on novel perovskite oxygen carrier materials will offer new opportunities for the partial oxidation of CH4 and the decomposition of CO2 and / or H2O to produce syngas and H2 and / or CO, respectively. Summary of the Invention
[0020] This invention aims to provide a high-entropy perovskite-like oxygen carrier (La). 1-x A x {Co y (B1B2B3…B N ) 1-y}O 3-δ The preparation method of CH4 and CO2 and / or H2O and its application in the chemical chain reaction to produce syngas and CO and / or H2. That is, using a high-entropy perovskite oxygen carrier as a redox cycle active material, CH4 and CO2 and / or H2O are converted into syngas and CO and / or H2 respectively through a chemical chain reaction.
[0021] Another objective of this invention is to optimize the reaction parameters of high-entropy perovskite oxygen carriers in the partial oxidation of CH4 and decomposition of CO2 and / or H2O in a chemical chain to prepare syngas and CO and / or H2, thereby providing optimal reaction conditions.
[0022] To achieve the above objectives, the present invention provides the following aspects:
[0023] The high-entropy perovskite oxygen carrier (La) of the present invention 1-x A x {Co y (B1B2B3…B N ) 1-y}O 3-δThe high-entropy perovskite oxygen carrier is characterized by the following composition: its A-position consists of one or more rare earth metal ions, alkaline earth metal ions, or main group metal ions such as La, Nd, Sm, Gd, Dy, Y, Ce, Pr, Sr, Ca, Ba, Mg, and Bi; and its B-position consists of three or more transition metal ions, main group metal ions, or alkaline earth metal ions such as Fe, Mn, Cu, Ni, Cr, Zn, Sc, Zr, Nb, Hf, Ce, Ti, V, W, Al, Ga, and Mg, to ensure that the structural entropy of the high-entropy perovskite oxygen carrier is greater than 1.5R.
[0024] The preparation method of the high-entropy perovskite oxygen carrier is one of the following: sol-gel combustion method and high-temperature solid-phase reaction; wherein,
[0025] The synthesis steps of the sol-gel combustion method are as follows:
[0026] Salt ACl of A was weighed according to the molar ratio x:(1-x):y:(1-y) / N. m Or A(NO3) m La(NO3)3 or LaCl3, Co(NO3)2 or CoCl2, and different elements at the B site: B1, B2, B3…B N salt BCl n Or B(NO3) n The amount of chelating agent is calculated based on the molar amount of the metal ions. The chelating agent is selected from one or more of glycine, citric acid, urea, and vinyl alcohol. The molar ratio of the chelating agent to the metal ions is 1.0-6.0 (preferably 1.5-4.0, more preferably 2.0-3.5). 1-15 mL / mmol of deionized water is added to dissolve the metal salt mixture. The mixture is stirred evenly, ultrasonically dispersed, and aged for 1-3 hours. Excess water is evaporated to a gel state. The gel is transferred to a 110°C oven and dried for 12 hours to obtain a dry gel. The dry gel is then placed in a muffle furnace at 300-500°C, ignited, and calcined for 30 minutes. It is then calcined at 700-1500°C (preferably 750-1400°C, more preferably 800-1300°C) for 3-24 hours (preferably 6-12 hours). After cooling to room temperature, the solid product is ground to obtain an oxygen carrier material, or it is calcined again at 700-1500°C for 3-12 hours. After h, the solid product is ground and pulverized to obtain the oxygen carrier material;
[0027] The synthesis steps of the high-temperature solid-state reaction are as follows:
[0028] Salt A2(CO3) of A was weighed according to the molar ratio of metal elements x:(1-x):y:(1-y) / N. m or oxide A2O mLa2(CO3)3 or La2O3, Co3O4 or CoO or CoCO3, with different elements at the B site: B1, B2, B3…B N Salt B2(CO3) n or oxide B2O n The mixture is ground evenly in a mortar and pestle, and then heated to 700-1500℃ (preferably 750-1400℃, more preferably 800-1300℃) at a rate of 1-25℃ / min under a set atmosphere and calcined for 3-24 h (preferably 6-12 h). After cooling to room temperature, the resulting solid product is ground and pulverized to obtain an oxygen carrier material, or it is calcined again at 700-1500℃ for 3-12 h and then the solid product is ground and pulverized to obtain an oxygen carrier material. The atmosphere consists of a mixture of 0-100% air and 100-0% CO2 by volume, and the total gas flow rate is set to 50-200 mL / min.
[0029] The application of the high-entropy perovskite oxygen carrier in the chemical chain conversion of CH4 with CO2 and / or H2O to prepare syngas and CO and / or H2 is characterized in that the partial oxidation of CH4 and the decomposition of CO2 and / or H2O in the chemical chain reaction are carried out in a fixed-bed reactor. The specific operation of the chemical chain reaction is as follows: weigh about 0.1-1.0g of high-entropy perovskite oxygen carrier active material and fill the oxygen carrier into a corundum or quartz fixed-bed reactor as required. The temperature of the fixed-bed reactor is heated from room temperature to 400-1000℃ at a heating rate of 5-20℃ / min under an N2 or Ar atmosphere. Then, a CH4-N2 mixture with a methane volume content of 1-100% is introduced at a flow rate of 10-500 mL / min under isothermal conditions to carry out the partial oxidation of methane to syngas for 1-20 min. Next, the reaction temperature of the fixed bed reactor is adjusted to 400-1000℃ under an N2 or Ar atmosphere, and a mixture of carbon dioxide and / or water vapor with a volume content of 1-100% and N2 or Ar as the equilibrium gas is introduced at a flow rate of 10-500 mL / min under isothermal conditions. The rate is increased to mL / min until the CO and / or H2 production reaction ends. The high-entropy perovskite oxygen carrier is regenerated by a cyclic reaction of partial oxidation with CH4 and decomposition with CO2 and / or H2O. The regenerated high-entropy perovskite oxygen carrier then undergoes a cyclic reaction of partial oxidation with CH4 and decomposition with CO2 and / or H2O.
[0030] The application of the high-entropy perovskite oxygen carrier in the chemical chain conversion of CH4 with CO2 and / or H2O to prepare syngas and CO and / or H2 is characterized by the high-entropy perovskite oxygen carrier having good anti-carbon deposition properties, no carbon deposition in the partial oxidation reaction of CH4, the molar ratio of H2 / CO in the syngas being close to the theoretical ratio n(H2) / n(CO)=2:1, and the syngas selectivity being as high as 100%, making it particularly suitable for the Fischer-Tropsch synthesis reaction to prepare methanol.
[0031] The application of the high-entropy perovskite oxygen carrier in the chemical chain conversion of CH4 with CO2 and / or H2O to produce syngas and CO and / or H2 is characterized in that the fixed-bed reactor is made of either corundum or quartz; wherein the corundum fixed-bed reactor has a straight-tube structure: including a corundum tube, a corundum crucible with an open top and a perforated bottom inside the corundum tube, a supporting corundum tube below the corundum crucible, and the corundum crucible being positioned in the isothermal zone inside the outer corundum tube by the supporting corundum tube below it; the bottom of the corundum crucible is filled with an appropriate amount of quartz. The quartz fixed-bed reactor is constructed by sequentially filling oxygen-carrying active material and alumina microspheres above quartz wool. The reactor can be either a straight tube or a U-shaped tube. In the straight tube type, the bottom of the isothermal zone is tapered to a certain extent, with quartz wool filling the tapered area, followed by the sequential filling of oxygen-carrying active material and alumina microspheres. In the U-shaped tube type, the isothermal zone is a constant-diameter reactor, with the oxygen-carrying active material filling the isothermal zone located at the bottom or fixed positions on both sides of the U-shaped tube. Both ends are sealed with quartz wool and alumina microspheres in sequence.
[0032] The present invention has the following advantages:
[0033] 1. This invention utilizes high-entropy perovskite-type oxygen carrier La 1-x A x {Co y (B1B2B3…B N ) 1-y}O 3-δ As a redox cycle active material, this high-entropy perovskite oxygen carrier, through a two-step chemical chain reaction involving the partial oxidation of CH4 and the decomposition of CO2 and / or H2O to produce syngas and CO and / or H2, can produce higher yields of syngas (≤ 800 °C) at lower temperatures compared to other types of oxygen carrier materials. o C, 10-200 mL / g), and the partial oxidation reaction of CH4 produces no carbon deposits. The molar ratio of H2 / CO in the syngas is close to the theoretical ratio n(H2) / n(CO)=2:1, and the syngas selectivity is as high as 100%, which is especially suitable for the reverse synthesis of methanol by Fischer-Tropsch.
[0034] 2. The high-entropy perovskite oxygen carrier La provided by this invention 1-x Ax {Co y (B1B2B3…B N ) 1-y}O 3-δ The synthesis method is simple, it has good high-temperature stability, and it is easy to synthesize on a large scale; the reduced oxygen carrier La rich in oxygen vacancy defects 1-x A x {Co y (B1B2B3…B N ) 1-y}O 3-δred Within a wide temperature range (600-1000) o C) All of them have good CO2 and / or H2O decomposition reactivity, and their CO and / or H2 yield per unit mass is high. The reduced oxygen carrier is simultaneously re-oxidized to the initial state, completing the regeneration and restoration, thereby realizing the multiple recycling of oxygen carrier materials.
[0035] 3. The high-entropy perovskite oxygen carrier La provided by this invention 1-x A x {Co y (B1B2B3…B N ) 1-y}O 3-δ In the chemical chain of partial oxidation of CH4 and decomposition of CO2 and / or H2O to produce syngas and CO and / or H2, the high-temperature heat energy generated by solar focusing or industrial waste heat recovery is used as the energy source. CH4, CO2 and / or H2O are used as the basic chemical reaction raw materials to produce high-value-added syngas, CO and / or H2 products without any other by-products. It is a sustainable and clean energy conversion system. Attached Figure Description
[0036] Figure 1 The diagram shown is a simplified structural diagram of a corundum fixed-bed reactor, where 1: corundum tube; 2: supporting corundum tube; 3: sealing joint; 4: corundum crucible; 5: oxygen carrier active material.
[0037] Figure 2 La for different structural entropies 1-x A x {Co y (B1B2B3…B N ) 1-y}O 3-δ The XRD characteristic diagram of the oxygen carrier (x=0-1, y=0-1, δ=0-2, N≥1) shows that the synthesized perovskite oxygen carrier has a typical rhombohedral perovskite structure.
[0038] Figure 3 For La 0.8 Sr 0.2Co 0.25 Ni 0.25 Fe 0.25 Ga 0.25 O 3-δox Real-time rate curve of gas release during the partial oxidation half-reaction of CH4 at 800℃.
[0039] Figure 4 For La 0.8 Sr 0.2 Co 0.25 Ni 0.25 Fe 0.25 Ga 0.25 O 3-δred Real-time rate curve of gas release during the CO2 decomposition half-reaction under oxygen carrier conditions at 800℃. Detailed Implementation
[0040] A simplified structural diagram of the corundum fixed-bed reactor is attached. Figure 1 In application, weigh 0.1-10.0 g of high-entropy perovskite oxygen carrier and place it in a corundum crucible. The sample loading method is as described above. The reactor material is a corundum tube with an inner diameter of 15-20 mm. The reaction products are analyzed online qualitatively and quantitatively using a gas detector or gas chromatography.
[0041] Example 1 (using La) 0.8 Sr 0.2 Co 0.25 Ni 0.25 Fe 0.25 Ga 0.25 (Taking O3 as an example)
[0042] Weigh 3.4643 g (8 mmol) La(NO3)3.6H2O, 0.4233 g (2 mmol) Sr(NO3)2, 0.2910ng (nmmol, n = 0-10) Co(NO3)2.6H2O, 0.09694(10-n) g ((10-n) / 3 mmol) Ni(NO3)2.6H2O, 0.1347(10-n) g ((10-n) / 3 mmol) Fe(NO3)3.9H2O, 0.1393(10-n) g ((10-n) / 3 mmol) Ga(NO3)3.9H2O and 7.3549 g (35 mmol) C6H8O7·H2O is dissolved in 20-100 In mL of deionized water, the mixture was stirred evenly at room temperature, ultrasonically dispersed, and aged for 1-3 hours. Excess water was then evaporated at 60-100℃ until a gel was formed. The gel was transferred to a 110℃ oven and dried for 12 hours to obtain a dry gel. This dry gel was then placed in a muffle furnace at 300-500℃, ignited, and calcined for 30 minutes, followed by calcination at 700-1500℃ for 3-24 hours. After cooling to room temperature, the solid product was ground to obtain La. 0.8 Sr 0.2 Co 0.25 Ni 0.25 Fe 0.25 Ga 0.25 O3 oxygen carrier material, or after calcining it again at 700-1500℃ for 3-12 h, the solid product is ground and pulverized to obtain La. 0.8 Sr 0.2 Co 0.25 Ni 0.25 Fe 0.25 Ga 0.25 O3 oxygen carrier materials. Different types of rare earth metal, alkaline earth metal, or main group metal nitrates (such as one or more of La, Nd, Sm, Gd, Dy, Y, Ce, Pr, Sr, Ca, Ba, Mg, Bi, etc.) and transition metal, main group metal, or alkaline earth metal nitrates (such as three or more of Fe, Mn, Cu, Ni, Cr, Zn, Sc, Zr, Nb, Hf, Ce, Ti, V, W, Al, Ga, Mg, etc.) are selected as A-site and B-site constituent elements, respectively. The composition and doping ratio (0-100 atom %) of different elements at the A-site and B-site are adjusted to obtain a series of A-site and B-site doped and modified La. 1-x A x {Co y (B1B2B3…B N ) 1-y}O 3-δ Perovskite oxygen carrier, with Figure 2XRD feature maps of perovskite oxygen carriers with different structural entropies.
[0043] Example 2 (using La) 0.8 Sr 0.2 Co 0.25 Ni 0.25 Fe 0.25 Al 0.25 (Taking O3 as an example)
[0044] Weigh out 2.9710 g (8 mmol) LaCl3·7H2O, 0.5332 g (2 mmol) SrCl2·6H2O, 0.2379 ng (n mmol, n = 0-10) CoCl2·6H2O, 0.07923 (10-n) g ((10-n) / 3 mmol) NiCl2·6H2O, 0.0901 (10-n) g ((10-n) / 3 mmol) FeCl3·9H2O, 0.08048 (10-n) g ((10-n) / 3 mmol) AlCl3·6H2O, and 7.3549 g (35 mmol) C6H8O7·H2O, and dissolve them in 20-100 mL of water. In mL of deionized water, the mixture was stirred evenly at room temperature, ultrasonically dispersed, and aged for 1-3 hours. Excess water was then evaporated at 60-100℃ until a gel was formed. The gel was transferred to a 110℃ oven and dried for 12 hours to obtain a dry gel. This dry gel was then placed in a muffle furnace at 300-500℃, ignited, and calcined for 30 minutes, followed by calcination at 700-1500℃ for 3-24 hours. After cooling to room temperature, the solid product was ground to obtain La. 0.8 Sr 0.2 Co 0.25 Ni 0.25 Fe 0.25 Al 0.25 O3 oxygen carrier material, or after calcining it again at 700-1500℃ for 3-12 h, the solid product is ground and pulverized to obtain La. 0.8 Sr 0.2 Co 0.25 Ni 0.25 Fe 0.25 Al 0.25O3 oxygen carrier materials. Different types of rare earth metal, alkaline earth metal, or main group metal nitrates (such as one or more of La, Nd, Sm, Gd, Dy, Y, Ce, Pr, Sr, Ca, Ba, Mg, Bi, etc.) and transition metal, main group metal, or alkaline earth metal nitrates (such as three or more of Fe, Mn, Cu, Ni, Cr, Zn, Sc, Zr, Nb, Hf, Ce, Ti, V, W, Al, Ga, Mg, etc.) are selected as A-site and B-site constituent elements, respectively. The composition and doping ratio (0-100 atom %) of different elements at the A-site and B-site are adjusted to obtain a series of A-site and B-site doped and modified La. 1-x A x {Co y (B1B2B3…B N ) 1-y}O 3-δ Perovskite oxygen carrier.
[0045] Example 3 (using La) 0.8 Sr 0.2 Co 0.25 Ni 0.25 Fe 0.25 Ga 0.25 (Taking O3 as an example)
[0046] Weigh out 1.3033 g (4 mmol) La₂O₃, 0.2953 g (2 mmol) SrCO₃, 0.2408 ng (n mmol, n = (0-10) / 3) Co₃O₄, 0.02490 (10⁻³n) g ((10⁻³n) / 3 mmol) NiO, 0.02573 (10⁻³n) g ((10⁻³n) / 9 mmol) Fe₃O₄, and 0.03124 (10⁻³n) g ((10⁻³n) / 6 mmol) Ga₂O₃; grind them evenly in a mortar and pestle, and then grind them at 1-25°C under a controlled atmosphere. o Heating to 700-1500℃ at a rate of C / min, calcining for 3-24 h, and then cooling to room temperature, the resulting solid product is ground to obtain La. 0.8 Sr 0.2 Co 0.25 Ni 0.25 Fe 0.25 Ga 0.25 O3 oxygen carrier material, or place it again at 700-1500 oAfter calcination at C for 3-12 h, the solid product is ground and pulverized to obtain the corresponding oxygen carrier material. The atmosphere consists of a mixture of 0-100% air and 100-0% CO2 by volume, with a total gas flow rate of 50-200 mL / min. Different types of rare earth metal, alkaline earth metal, or main group metal nitrates (such as one or more of La, Nd, Sm, Gd, Dy, Y, Ce, Pr, Sr, Ca, Ba, Mg, Bi, etc.) and transition metal, main group metal, or alkaline earth metal nitrates (such as three or more of Fe, Mn, Cu, Ni, Cr, Zn, Sc, Zr, Nb, Hf, Ce, Ti, V, W, Al, Ga, Mg, etc.) are selected as the A-site and B-site constituent elements, respectively. The composition and doping ratio (0-100 atom %) of different elements at the A-site and B-site are adjusted to obtain a series of A-site and B-site doped and modified La. 1-x A x {Co y (B1B2B3…B N ) 1-y}O 3-δ Perovskite oxygen carrier.
[0047] Example 4
[0048] Weigh approximately 0.1-10.0 g of the high-entropy perovskite oxygen carrier active material synthesized in Examples 1-3, and pack the oxygen carrier into a corundum or quartz fixed-bed reactor as required. Under a N2 or Ar atmosphere, heat the fixed-bed reactor from room temperature to 400-1000°C at a heating rate of 5-20°C / min. Then, under constant temperature conditions, introduce a CH4-N2 mixture with a CH4 volume content of 1-100% at a flow rate of 10-1000 mL / min to perform a partial oxidation of CH4 to prepare syngas for 1-20 min. Next, under a N2 or Ar atmosphere, adjust the reaction temperature of the fixed bed to 400-1000°C, and then, under constant temperature conditions, introduce a mixture of carbon dioxide and / or water vapor with a volume content of 1-100% and N2 or Ar as the equilibrium gas at a flow rate of 10-1000 mL / min until the CO and / or H2 production reaction is complete. (Appendix) Figure 3 and 4 The table shows the rate-time curves of syngas production and CO production reactions in the partial oxidation of CH4 and decomposition of CO2 synthesized in Example 1. The high-entropy perovskite oxygen carrier is regenerated through a cyclic reaction of partial oxidation of CH4 and decomposition of CO2 and / or H2O. The regenerated high-entropy perovskite oxygen carrier then undergoes a cyclic reaction of partial oxidation of CH4 and decomposition of CO2 and / or H2O. Table 1 shows the La values for different structural entropies. 1-x Ax {Co y (B1B2B3…B N ) 1-y}O 3-δ (x=0-1, y=0-1, δ=0-2, n) B =(1-y) / N, N≥1) Performance results of oxygen carrier chemical chain cycle CH4 partial oxidation and CO2 and / or H2O decomposition reaction.
[0049] In summary, this invention has created a series of high-entropy perovskite-based oxygen carrier materials, which produce syngas and CO and / or H2 products through a two-step chemical chain reaction involving partial oxidation of CH4 and decomposition of CO2 and / or H2O. This invention utilizes high-entropy perovskite-based oxygen carriers (La... 1-x A x {Co y (B1B2B3…B N ) 1-y}O 3-δ As an oxygen carrier active material, a two-step chemical chain reaction is used to partially oxidize CH4 and decompose CO2 and / or H2O to prepare syngas and CO and / or H2. The high-entropy perovskite oxygen carrier provided by this invention has a simple synthesis method, good high-temperature stability, and is easy to synthesize on a large scale; the reduced oxygen carrier La, rich in oxygen vacancy defects... 1-x A x {Co y (B1B2B3…B N ) 1-y}O 3-δred This invention exhibits excellent chemical chain reaction performance over a wide temperature range (700-1000℃). The syngas selectivity of the partial oxidation half-reaction of CH4 reaches up to 100%, while the CO and / or H2 decomposition half-reaction yields high levels of CO and / or H2. Simultaneously, the reduced oxygen carrier is re-oxidized to its initial state, completing regeneration and restoration. The high-entropy perovskite oxygen carrier chemical chain reaction system provided by this invention utilizes high-temperature heat energy generated by solar focusing or industrial waste heat recovery as an energy source. Using CH4, CO2, and / or H2O as basic chemical reaction raw materials, it produces high-value-added syngas, CO, and / or H2 products. The reaction process is clean and pollution-free, and it is expected to become an effective technology for achieving efficient conversion of CH4 with CO2 and / or H2O using solar thermal or industrial waste heat to prepare high-value-added chemicals and chemical fuels (such as CO / H2).
[0050] Table 1. La of different structural entropies 1-x A x {Co y (B1B2B3…B N ) 1-y}O 3-δ(x=0-1, y=0-1, δ=0-2, n) B =(1-y) / N, N≥1) Oxygen carrier chemical chain cycle CH4 partial oxidation and CO2 and / or H2O decomposition reaction performance a
[0051]
[0052]
[0053]
[0054] a The volume concentration of CH4 used in the partial oxidation reaction of CH4 is 5%, and the volume concentration of CO2 and / or H2O used in the decomposition reaction of CO2 and / or H2O is 5%. b CH4 partial oxidation reaction time; c CO2 and / or H2O decomposition reaction time; d Oxygen carrier re-oxidation reaction temperature.
Claims
1. The application of a high-entropy perovskite oxygen carrier in the chemical chain conversion of CH4 with CO2 and / or H2O to prepare syngas and CO and / or H2, characterized in that, The chemical formula of this high-entropy perovskite oxygen carrier is La. 1-x A x {Co y (B1B2B3…B N ) 1-y }O 3-δ Given x=0-1, y=0-1, δ=0-2, N≥3, and N is an integer, its lattice structure entropy value S c >1.5R, where R is the gas constant; this high-entropy perovskite oxygen carrier exhibits excellent anti-carbon deposition properties, with no carbon deposition forming during the partial oxidation of CH4. The H2 / CO molar ratio of the syngas products is close to the theoretical ratio n(H2) / n(CO) = 2:1, and the syngas selectivity is ≥98%, making it particularly suitable for Fischer-Tropsch synthesis to prepare methanol. The aforementioned chemical chain CH4 to CO2 and / or H2O conversion reaction system consists of the following two basic reaction steps: (1) Oxidized La 1-x A x {Co y (B1B2B3…B N ) 1-y }O 3-δox The oxygen carrier first reacts with CH4, and methane is partially oxidized to CO and H2. Simultaneously, this oxidized oxygen carrier is reduced to a reduced state, La, rich in oxygen vacancy defects. 1-x A x {Co y (B1B2B3…B N ) 1-y }O 3-δred The oxygen carrier is reacted at a temperature of 500-1000℃ (preferably 600-900℃, more preferably 750-850℃). (2) Reduced La rich in oxygen vacancy defects 1-x A x {Co y (B1B2B3…B N ) 1-y }O 3-δred The oxygen carrier then reacts with CO2 and / or H2O to produce CO and / or H2. Simultaneously, the reduced oxygen carrier is regenerated into oxidized La. 1-x A x {Co y (B1B2B3…B N ) 1-y }O 3-δox The oxygen carrier is reacted at a temperature of 600-1000℃ (preferably 700-900℃, more preferably 750-850℃). Through the above chemical chain reaction system, CH4 is partially oxidized to syngas, i.e., a mixture of CO and H2, while CO2 and / or H2O are reduced to CO and / or H2. 1-x A x {Co y (B1B2B3…B N ) 1-y }O 3-δox The oxygen carrier is regenerated and restored through a chemical chain reaction, and then the various reaction steps of the chemical chain reaction system continue to cycle.
2. The application of the high-entropy perovskite oxygen carrier according to claim 1 in the chemical chain conversion of CH4 with CO2 and / or H2O to prepare syngas and CO and / or H2, characterized in that, The A-site and / or B-site of the high-entropy perovskite oxygen carrier are extensively doped with different metal ions, wherein A is one or more of alkali metal, alkaline earth metal, or main group metal ions La, Nd, Sm, Gd, Dy, Y, Ce, Pr, Sr, Ca, Ba, Mg, and Bi; and B is three or more of transition metal, main group metal, or alkaline earth metal ions Fe, Mn, Cu, Ni, Cr, Zn, Sc, Zr, Nb, Hf, Ce, Ti, V, W, Al, Ga, and Mg. The stoichiometric coefficient of the different B-site doped metal ions is n. B =(1-y) / N, by adjusting the doping ratio of different elements at the A-site and / or B-site to 0-100 atom%, a series of high-entropy perovskite oxygen carriers modified by A-site and / or B-site doping were obtained.
3. The application of the high-entropy perovskite oxygen carrier according to claim 1 in the chemical chain conversion of CH4 with CO2 and / or H2O to prepare syngas and CO and / or H2, characterized in that, The lattice entropy value S of the high-entropy perovskite oxygen carrier c =k B ln(Ω) = -R >1.5R, k B Here, is the Boltzmann constant, and R is the gas constant. Let be the molar concentration of component i.
4. The application of the high-entropy perovskite oxygen carrier according to claim 1 in the chemical chain conversion of CH4 with CO2 and / or H2O to prepare syngas and CO and / or H2, characterized in that, The preparation method of the high-entropy perovskite oxygen carrier is either a sol-gel combustion method or a high-temperature solid-phase reaction; wherein, The synthesis steps of the sol-gel combustion method are as follows: Salt ACl of A is weighed using an analytical balance according to the molar ratio x:(1-x):y:(1-y) / N. m Or A(NO3) m La(NO3)3 or LaCl3, Co(NO3)2 or CoCl2, and different elements at the B site: B1, B2, B3…B N salt BCl n Or B(NO3) n The amount of chelating agent is calculated based on the molar amount of the metal ion. The chelating agent is selected from one or more of glycine, citric acid, urea, and vinyl alcohol. The molar ratio of the chelating agent to the metal ion is 1.0-6.0 (preferably 1.5-4.0, more preferably 2.0-3.5); 1-15 The metal salt mixture was dissolved in deionized water at a concentration of mL / mmol of the salt compound, stirred evenly, ultrasonically dispersed, and aged for 1-3 hours. After evaporation, excess water was removed to obtain a gel. The gel was then transferred to an oven at 110°C and dried for 12 hours to obtain a dry gel. The dry gel was then placed in a muffle furnace at 300-500°C, ignited, and calcined for 30 minutes. It was then calcined at 700-1500°C (preferably 750-1400°C, more preferably 800-1300°C) for 3-24 hours (preferably 6-12 hours). After cooling to room temperature, the solid product was ground to obtain an oxygen carrier material. Alternatively, the solid product could be calcined again at 700-1500°C for 3-12 hours and then ground to obtain an oxygen carrier material. The synthesis steps of the high-temperature solid-state reaction are as follows: Weigh out salt A2(CO3) of A according to the molar ratio of metal elements x:(1-x):y:(1-y) / N. m or oxide A2O m La2(CO3)3 or La2O3, Co3O4 or CoO or CoCO3, with different elements at the B site: B1, B2, B3…B N Salt B2(CO3) n or oxide B2O n The mixture is ground evenly in a mortar and pestle, and then heated to 700-1500℃ (preferably 750-1400℃, more preferably 800-1300℃) at a rate of 1-25℃ / min under a set atmosphere and calcined for 3-24h (preferably 6-12h). After cooling to room temperature, the resulting solid product is ground and pulverized to obtain an oxygen carrier material, or it is calcined again at 700-1500℃ for 3-12h and then the resulting solid product is ground and pulverized to obtain an oxygen carrier material. The atmosphere consists of a mixture of 0-100% air and 100-0% CO2 by volume, and the total gas flow rate is set to 50-200 mL / min.
5. The application of the high-entropy perovskite oxygen carrier according to claim 1 in the chemical chain conversion of CH4 with CO2 and / or H2O to prepare syngas and CO and / or H2, characterized in that, The partial oxidation of CH4 and decomposition of CO2 and / or H2O in this chemical chain reaction is carried out in a fixed-bed reactor. The specific operation of this chemical chain reaction is as follows: Weigh approximately 0.1-10.0 g of high-entropy perovskite oxygen carrier active material and fill the oxygen carrier into a corundum or quartz fixed-bed reactor as required. Under a N2 or Ar atmosphere, heat the temperature of the fixed-bed reactor from room temperature to 400-1000℃ at a heating rate of 5-20℃ / min. Then, under constant temperature conditions, introduce a CH4-N2 mixture with a methane volume content of 1-100% at a flow rate of 10-500 mL / min to carry out the partial oxidation of methane to prepare syngas for 1-20 min. Then, under the protection of a N2 or Ar atmosphere, adjust the reaction temperature of the fixed bed to 400-1000℃, and under constant temperature conditions, introduce a mixture of carbon dioxide and / or water vapor with a volume content of 1-100% and N2 or Ar as the equilibrium gas at a flow rate of 10-500 mL / min. The rate is increased to mL / min until the CO and / or H2 production reaction ends; the high-entropy perovskite oxygen carrier is regenerated by a cyclic reaction of partial oxidation with CH4 and decomposition with CO2 and / or H2O, and the regenerated high-entropy perovskite oxygen carrier is then subjected to a cyclic reaction of partial oxidation with CH4 and decomposition with CO2 and / or H2O.
6. The application of the high-entropy perovskite oxygen carrier according to claims 1 and 4 in the chemical chain conversion of CH4 with CO2 and / or H2O to prepare syngas and CO and / or H2, characterized in that, The fixed-bed reactor is made of either corundum or quartz. The corundum fixed-bed reactor has a straight-tube structure, comprising a corundum tube with an open top and a perforated bottom. A supporting corundum tube is located below the crucible, positioning it within the isothermal zone of the outer corundum tube via this supporting tube. The bottom of the crucible is filled with quartz wool, and oxygen-carrying active material and alumina microspheres are sequentially placed above the quartz wool. The quartz fixed-bed reactor has a structure that is either straight-tube or U-shaped. The straight-tube quartz reactor has a tapered bottom in its isothermal zone, with quartz wool filling the tapered area, followed by oxygen-carrying active material and alumina microspheres. The U-shaped quartz reactor is a constant-diameter reactor, with the isothermal zone filled with oxygen-carrying active material at the bottom or fixed positions on either side of the U-shaped tube. Both ends are sealed with quartz wool and alumina microspheres sequentially.